Exploring the city as text and dominant discourse place - Mojtaba Valibeigi (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
The study has tried to answer the question of how the dominant discourse in the city tries to create meanings and forms an interpretation by using signs and symbols. Accordingly, common semiotics of Dur Untash city has been investigated. In three steps, including preparation, organization, and final report or conclusion, a content analysis method has been done. First, deconstruction views of reading place are explained and how an interpretation discourse is formed. Then we investigated some standard semantic features of Dur Untash city and an image of some familiar ideas and signs is projected. Finally, a bipolar semantic interpretation of these signs and images is presented. The dominant discourse of the city has wanted to catch a meaning, but none of its symbols and characters has such a valid capacity and authority. Therefore, the dominant discourses could not conjure spatial features controlled by meaning-making